Experimental Study of Capture Effect for Medium Access Control with ALOHA. Issue 2 (1st April 2015) - Kosunalp, Selahattin; Mitchell, Paul D.; Grace, David; Clarke, Tim
Abstract : In this paper, we investigate the capture effect through experiments conducted with Iris nodes equipped with AT86RF230 radio transceivers. It is shown that the first arriving packet in a collision can capture the radio channel for equal power transmissions and may be decoded depending on the amount of overlap. A new 3‐packet‐capture scenario is introduced and implemented. To be able to understand the impact of capture on the throughput performance of wireless sensor networks, we present an analysis of the capture coefficient using our practical results. For real‐world implementations, the throughput of pure ALOHA considering a finite number of users is presented in analytical form. The capture coefficient is then applied to pure ALOHA as a case study. Using analytical and practical implementations of the capture effect on ALOHA, a very good match in channel throughput performance enhancement is demonstrated over the non‐capture effect case. TinyOS‐2.x is used to program the nodes and to observe data exchange on a computer through a base station.